1995
DOI: 10.1111/j.1365-2141.1995.tb05204.x
|View full text |Cite
|
Sign up to set email alerts
|

Autotumour reactive T‐cell clones among tumour‐infiltrating T lymphocytes in B‐cell non‐Hodgkin's lymphomas

Abstract: Seventy-three T-cell clones (TCC) were established from tumour-infiltrating lymphocytes-T (TIL-T) derived from lymph nodes involved by B-cell non-Hodgkin's lymphomas (B-NHL) in nine patients with different histological subtypes and clinical stages. 40 TCC (55%) expressed the CD25 Ag and were also able to proliferate in the presence of irradiated autologous B-NHL cells. Among them, 23 autotumour (AuTu) proliferative TCC were found not to proliferate to autologous EBV-transformed B-cell lines, indicating that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We previously reported that down-modulation of TCR-CD3 complexes on TCC before interaction with B-NHL or physical separation by Millipore membrane of both cell types resulted in neither activation nor expansion of TCC in response to malignant cells. These results demonstrate the necessity for cell-cell contact to induce activation of specific TCC and it is likely that TCR-HLA interactions were involved [2].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…We previously reported that down-modulation of TCR-CD3 complexes on TCC before interaction with B-NHL or physical separation by Millipore membrane of both cell types resulted in neither activation nor expansion of TCC in response to malignant cells. These results demonstrate the necessity for cell-cell contact to induce activation of specific TCC and it is likely that TCR-HLA interactions were involved [2].…”
Section: Discussionmentioning
confidence: 80%
“…The present study describes an autologous model derived from a follicular lymphoma biopsy developed to investigate the subsequent action of CD4 + T lymphocytes on tumoral B lymphocytes and therefore their role in B lymphoma development. Anti-tumoral CD4 + TCC derived from the intratumoral infiltrating T lymphocytes were obtained as previously described [2] and four clones were randomly selected. By use of non irradiated freshly isolated B-NHL cells, our model allowed not only cognate contact between B-NHL and CD4 + TCC but preserved signaling and subsequent response (such as cytokine production and cell surface expression of costimulatory and other molecules) in B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations